RELATIONS BETWEEN THE TRADITIONAL WOODEN SACRAL ARCHITECTURE OF THE PODHALE REGION AND CONTEMPORARY ARCHITECTURE OF CHURCHES - Kinga Palus (European Scientific Journal, ESJ, 2014)
The issues of building engineering in mountain regions, especially shaping sacral buildings over the centuries, beginning from traditional architecture of wooden Gothic churches to the churches built nowadays, form an interesting study topic. The Podhale region is both extremely difficult and interesting for modern authors of sacral parchitecture.The tradition of architectural works of wooden churches in Dębno, Obidowa, Grywałd and Harklowa created certain unique models of churches integrated with the conditions of the mountainous climate and landscape aspects. The article aims to answer the author's following question: when designing contemporary sacral buildings in the Podhale region are we to preserve the principles formed over the centuries, following the regional tradition of wooden Gothic churches or ones strictly connected with the style of Witkiewicz architecture, or shall we make attempts at their contemporary interpretation, at the same time preserving universal values so as not to lose the regional identity - continuity of tradition, which currently seems to be a signal of a crisis of our civilization?